Are the Most Prestigious Medical Journals Transparent Enough?. (September 2016) - Dal-Ré, Rafael
Abstract : The International Committee of Medical Journal Editors (ICMJE) has played a critical role in enhancing medical science reporting. Transparency in research is one of its most important objectives and the ICMJE has issued requirements for various stakeholders. However, ICMJE member journals have repeatedly failed to fully comply with a few transparency requirements.